Effect of dengue hemorrhagic fever on thrombomodulin level - Hendra Widjaja; Max F. J. Mantik (Indonesian Pediatric Society, 2009)
Background Thrombocyte and endothelial cells play animportant role in dengue hemorrhagic fever pathogenesis.Thrombomodulin is a part of glycoprotein membrane inendothelial cells. Therefore, thrombomodulin level willincrease if endothelial cells disruption occurs.Objective To acknowledge the correlation between thedegree of dengue hemorrhagic fever and thrombomodulinlevel.Methods This was a cross-sectional study. Subjects werehospitalized pediatric patients with age ranging from oneto 13 year old in pediatric ward at ProÂ£ Dr. R.D. KandouHospital, Manado, who had fever. Three milliliters of bloodwere taken from vein, and were divided for two tests whichwere routine blood analysis and thrombomodulin analysis.Different data resulted from the dengue hemorrhagic fevergroup were processed, and analyzed statistically using F Testand LSD (least significant difference) test. The relationbetween dengue hemorrhagic fever and thrombomodulinwas analyzed with Spearman correlation coefficient.Results There was a significant result in the difference ofthrombomodulin level on four dengue hemorrhagic fevergroups which were classified according to the severity ofdengue hemorrhagic fever. There was a very significantpositive correlation between the severity of denguehemorrhagic fever and thrombomodulin level in detectingendothelial cells impairment.Conclusion Thrombomodulin level can be used as amarker to detect endothelial cells impairment in denguehemorrhagic fever. Higher grade of dengue hemorrhagicfever will have higher thrombomodulin level.